The Interdiffusion Modeling of Aluminide Coated Ti-47Al-2Cr-2Nb-0.5Zr-0.5Y Intermetallic Alloy - F. Muhammad; E. A. Basuki; M. I. Juliansyah (Indonesian Journal of Physics, 2015)
In the present study, the interdiffusion behavior between coating layer and substrate of aluminide coated Ti- 47Al-2Cr-2Nb-0.5Zr-0.5Y intermetallic alloy were investigated at 800°C, 900°C, and 1000°C under argon atmosphere (closed system). The pack cementation, consists of 20%-wt. Al, 2%-wt. NH4Cl, and 78%-wt. Al2O3, was carried out at 900°C for 10 hours. The phases in the coatings, interdiffusion layer, and substrate were examined using optical microscope and scanning electron microscope (SEM) while the chemical composition were examined by Energy Dispersive X-Ray Spectroscopy (EDS) attached on the SEM. The interdiffusion coefficients were calculated according to Boltzmann-Matano method using the data obtained from EDS analyses. The calculated interdiffusion coefficients are 7.091 x 10-14, 1.650 x 10-12, and 5.261 x 10-12 cm2/s respectively for 800°C, 900°C, and 1000°C. The analytical and numerical method to predict the concentration profiles between coating layer, interdiffusion layer, and substrate. A reasonable agreement has been achieved between the experimental results and the simulated concentration profiles at every temperatures.